농촌 중년여성 비만원인 진단을 위한 사회생태학적 모형 기반 탐색적 연구 - 조희숙(Heui Sug Jo); 이종선(Jong Sun Lee); 정수미(Su Mi Jung); 드로니나 율리아(Yuliya Dronina); 박유경(Yu Kyung Park); 박양준(Yang Jun Park) (보건교육건강증진학회지, 2021)
Objectives: This study aimed to explore the causes of obesity among middle-ageed women in rural areas through a socio-ecological approach and propose strategies of obesity management. Methods: We selected two rural areas called the I and Y counties. For the quantitative aspect, secondary data and geospatial-analysis were used, whereas for the qualitative aspect, focus group interviews and official documents reviews were conducted. Results: Obesity was related more to low levels of physical activity (OR=1.811, p<.01) than to high levels. Groups that utilized nutritioin labels less tended to be more obese (OR=1.564, p<.05) than the other groups. The number of fast-food stores in the I county was twice as high as that in the Y county. The I county had poor conditions than the Y county in terms of public resources. The related factors could be divided in the following categories: (1) Body weight self-management; (2) Peers to exercise together; (3) Access to fresh food and exercise facility; (4) Health budget and lack of leisure programs. Conclusion: There were various obesity causes, and, thus, intervening one factor cannot be a proper solution. Therefore, a social-ecological approach should be utilized to address the obesity issues. KCI Citation Count: 0